Concept And Implementation Of Islamic Accounting: Theological Basis, Ulama's Perspective, And Comparison With Conventional Accounting - Juliasti Wulandari; Fenny Liani (Al-Fadilah: Islamic Economics Journal, 2024)
This study discusses the concept and implementation of Islamic accounting as an alternative financial system based on sharia values. By examining the principles of accounting in the Qur'an and Hadith as well as the interpretations of scholars, this study illustrates the theological and philosophical foundations that distinguish Islamic accounting from conventional accounting based on capitalism. The analysis includes philosophical differences, ethical approaches, the purpose of financial statements, and the relevance of Islamic values in modern accounting practices. In addition, this research also discusses the phenomenon of the development of sharia accounting in Indonesia and the world, the challenges of its implementation, as well as the potential and innovation in the digital era. The results of the study show that Islamic accounting is not only relevant to the needs of the contemporary economic system, but also has great potential as a fair and sustainable solution in answering global challenges.